How to Introduce Function Concept in Textbooks?:_x000D_ Evaluations of Pre-Service Mathematics Teachers - AKKOÇ, HATİCE; GÜLBAĞCI DEDE, HANDE (My University, 2020)
Textbooks are one of the most commonly used instructional resources by teachers. Using textbookswithout critical evaluation has a direct impact on instruction. For this reason, it is important to examine how preservice teachers evaluate and criticize textbooks. The aim of this study is to examine how pre-service mathematicsteachers evaluate the introductory sections of three different mathematics textbooks on functions each of whichembraces a different function idea. In the study, pre-service teachers’ written evaluation reports on the introductorysections were examined. It was found that they could evaluate the introductory sections of the books with a criticallens along with providing mathematical and pedagogical justification. However, a significant weakness of preservice teachers’ mathematical justifications is the difficulty in supporting their ideas about the limitations andaffordances of function ideas. A major weakness in pedagogical justifications was that the examples of daily lifewere privileged regardless of to what extent they represented the mathematical meaning of function.

Ders kitapları öğretmenlerin en çok kullandıkları ders materyalleri arasında yer almaktadır. Ders_x000D_ kitaplarının değerlendirilmeden derslerde birebir kullanılması öğretimi doğrudan etkilemektedir. Bu sebeple_x000D_ göreve başlayacak olan öğretmen adaylarının ders kitaplarını nasıl değerlendiklerinin incelenmesi önemlidir. Bu_x000D_ çalışmanın amacı matematik öğretmen adaylarının fonksiyona ait üç farklı fikri benimseyen üç farklı ders kitabını_x000D_ nasıl değerlendirdiklerini belirlemektir. Çalışmada adayların ders kitaplarının fonksiyona giriş bölümleri için_x000D_ yazdıkları değerlendirme raporları incelenmiştir. Çalışma sonucunda adayların ders kitaplarındaki farklı fonksiyon_x000D_ girişlerine matematiksel ve pedagojik gerekçeler göstererek eleştirel bir gözle bakabildikleri ortaya çıkmıştır. Buna_x000D_ rağmen adayların sundukları matematiksel gerekçeleri yeterli düzeyde açıklayamadığı görülmüştür. Ayrıca_x000D_ adayların giriş bölümlerinde var olan günlük hayat örneklerine çok fazla önem verdikleri fakat bu örneklerin_x000D_ fonksiyonu matematiksel olarak temsil edip etmediğini yeterince irdelemedikleri görülmektedir.
Ders Kitaplarında Fonksiyon Kavramına Nasıl Giriş Yapılıyor?: Matematik Öğretmen Adaylarının Değerlendirmeleri